Single cell transcriptomics comes of age - Sarah Aldridge (Nature Portfolio, 2020)
Single cell transcriptomics technologies have vast potential in advancing our understanding of biology and disease. Here, Sarah Aldridge and Sarah Teichmann review the last decade of technological advancements in single-cell transcriptomics and highlight some of the recent discoveries enabled by this technology.